2019
DOI: 10.1111/jch.13615
|View full text |Cite
|
Sign up to set email alerts
|

Utility of obesity and metabolic dyslipidemia (a non‐insulin based determinate of the metabolic syndrome and insulin resistance) in predicting arterial stiffness

Abstract: Increased arterial stiffening is not only a hallmark of the aging process but the consequence of many metabolic abnormalities such as insulin resistance (IR), obesity, and metabolic dyslipidemia. In patients with the cardiometabolic syndrome, arterial stiffening is consistently observed across all age groups. A core feature linking obesity and the metabolic syndrome to arterial stiffness has been IR. However, including other metabolic abnormalities such as metabolic dyslipidemia increases the risk prediction o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…We confirmed the two hypotheses that metabolic health and obesity phenotypes was associated with the development of arterial stiffness, and unhealthy individuals with either obesity or nonobesity status had a significantly higher risk of arterial stiffness than individuals with the MUNO phenotype, which did not exist in those with the MHO phenotype. The increase in the PWV with age in adulthood was reported to be not only due to the decrease in elasticity caused by the degeneration of the arterial wall but also the consequence of many metabolic abnormalities such as obesity and CAs [30]. Recent studies have demonstrated that the baPWV is associated with metabolic syndrome and increases with increasing numbers of metabolic syndrome components [23,31] .…”
Section: Discussionmentioning
confidence: 99%
“…We confirmed the two hypotheses that metabolic health and obesity phenotypes was associated with the development of arterial stiffness, and unhealthy individuals with either obesity or nonobesity status had a significantly higher risk of arterial stiffness than individuals with the MUNO phenotype, which did not exist in those with the MHO phenotype. The increase in the PWV with age in adulthood was reported to be not only due to the decrease in elasticity caused by the degeneration of the arterial wall but also the consequence of many metabolic abnormalities such as obesity and CAs [30]. Recent studies have demonstrated that the baPWV is associated with metabolic syndrome and increases with increasing numbers of metabolic syndrome components [23,31] .…”
Section: Discussionmentioning
confidence: 99%
“…In addition to plasma triglyceride and HDL‐C that are related to insulin‐mediated glucose disposal, the inclusion of BMI as a surrogate for visceral adiposity takes into account the causal relationship between adipose tissue inflammation and the development of IR and ultimately T2DM [ 37 - 39 ]. The nonlinear relationship we observed between baseline METS-IR and new-onset T2DM might be partly explained by the multifactorial interactions among adiposity, dysglycemia, and inflammation in metabolic pathways and vascular biologic processes [ 13 , 39 - 42 ]. Our findings echo previous literature on the nonlinear relationship between FPG and T2DM in the European population [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to plasma triglyceride and HDL-C that are related to insulin-mediated glucose disposal, the inclusion of BMI as a surrogate for visceral adiposity takes into account the causal relationship between adipose tissue inflammation and the development of IR and ultimately T2DM [37][38][39]. The nonlinear relationship we observed between baseline METS-IR and new-onset T2DM might be partly explained by the multifactorial interactions among adiposity, dysglycemia, and inflammation in metabolic pathways and vascular biologic processes [13,[39][40][41][42]. Our findings echo previous literature on the nonlinear relationship between FPG and T2DM in the European population [43].…”
Section: Relationship With Other Studiesmentioning
confidence: 96%